2011
DOI: 10.3171/2010.9.spine09865
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar total disc replacement from an extreme lateral approach: clinical experience with a minimum of 2 years' follow-up

Abstract: Object Current lumbar total disc replacement (TDR) devices require an anterior approach for implantation. This approach has inherent limitations, including risks to abdominal structures and the need for resection of the anterior longitudinal ligament (ALL). Placement of a TDR device from a true lateral (extreme lateral interbody fusion [XLIF]) approach is thought to offer a less invasive option to access the disc space, preserving the stabilizing ligaments and avoidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 29 publications
0
66
0
Order By: Relevance
“…However, the determination of absolute prevalence of deficits and their natural history as well as contributing factors remains incomplete and controversial in the literature. Overall, the number of postoperative neurologic events ranges in literature between 0.6 and 33.6% after LLIF [10,11,[13][14][15][16]. In a study by Tohmeh et al [12] 28% of patients experienced a new iliopsoas weakness and 18% claimed of sensory loss at the upper medial thigh although intra-operative real-time monitoring was used to prevent neurologic deficits after LLIF.…”
Section: Discussionmentioning
confidence: 99%
“…However, the determination of absolute prevalence of deficits and their natural history as well as contributing factors remains incomplete and controversial in the literature. Overall, the number of postoperative neurologic events ranges in literature between 0.6 and 33.6% after LLIF [10,11,[13][14][15][16]. In a study by Tohmeh et al [12] 28% of patients experienced a new iliopsoas weakness and 18% claimed of sensory loss at the upper medial thigh although intra-operative real-time monitoring was used to prevent neurologic deficits after LLIF.…”
Section: Discussionmentioning
confidence: 99%
“…The complications were broken down into sensory (dysethesia, paraesthesia, or hypoesthesia), motor (distal weakness), and muscular (iliopsoas weakness or hematoma) deficits. The results are summarized in Tables 4 and 5. 1,2,4,7,9,10, [16][17][18][19]21,23,24,26,29,30,32 Mayer previously described an oblique MIS access to the L2-5 discs through a retroperitoneal approach and a transperitoneal approach to access the L5-S1 disc. 20 Saraph et al compared a traditional open anterior approach with Mayer's MIS approach and found that although fusion and complication rates were similar in their study, the MIS group had shorter operating time, less blood loss, and decreased postoperative pain.…”
Section: 1019mentioning
confidence: 99%
“…15,27 The lateral transpsoas MIS approach, first described by Pimenta et al, does not require an access surgeon and allows for access to the spine without the need to mobilize the great vessels or sympathetic nerves. 19,23,33 Access to the spine is gained through a far-lateral incision that enters the retroperitoneal space and requires dissection through the psoas muscle. The most devastating injury is femoral nerve palsy with complete loss of quadriceps strength.…”
Section: 1019mentioning
confidence: 99%
“…Studies from our systematic review that have characterized the complications of lateral transpsoas approaches (Table 2) included adverse medical outcomes (ileus, pneumonia, renal, pulmonary embolus, cardiac [26,27], anemia, volvulus [27], rhabdomyolysis [7], pleural effusion, sepsis [12]) and surgery-specific complications (vertebral fracture [14,26,27,32], end plate fracture [27], iatrogenic herniated nucleus pulposus [27], graft subsidence [7], sensory disturbance [14-16, 20, 26, 32, 33], Yes XLIF = extreme lumbar interbody fusion; ALIF = anterior lumbar interbody fusion; TDR = total disc replacement; fx = fracture; DDD = degenerative disc disease; HNP = herniated nucleus pulposus; EP = endplate; VB = vertebral body; OP = osteophyte; MI = myocardial infarction; DVT = deep venous thrombosis; PE = pulmonary embolism; A fib = atrial fibrillation; CSF = cerebrospinal fluid. motor deficits [12, 14-16, 20, 26, 27, 32, 33], incisional hernias [4,26], hardware failures [12,27], loss of fixation [15], malpositioned cage, retroperitoneal hemorrhage [32], hematoma [27],wound infection [12,20], durotomy, pneumothorax, and peritoneum perforation [33]). Second, none of the literature reviewed was of high quality.…”
Section: Discussionmentioning
confidence: 99%
“…The average reported followup ranged from 2 days to 24 months [7, 12-16, 20, 26, 27, 32-34, 36]. VAS pain score, reported in eight of 13 studies, improved on average from 8.3 to 3.6, and ODI, reported in five of 13 studies, improved on average from 48.1 to 27.3 [7,13,14,16,20,27,32,34,36].…”
Section: Discussionmentioning
confidence: 99%